Network position and innovation capability in the regional innovation network. Issue 9 (2nd September 2019) - Piazza, Mariangela; Mazzola, Erica; Abbate, Lorenzo; Perrone, Giovanni
ABSTRACT: This paper investigates the positioning of actors characterized by different natures in a regional innovation network and explores how these actors improve their innovation capabilities by assuming prominence or brokering positions. Innovation capability is widely seen to be the driving force in building regional competitive advantage, therefore investigating how the positioning of actors improves their innovation-related activities is relevant in terms of regional competitiveness. This paper builds on a survey conducted on the Sicilian regional area in Italy. A questionnaire was used to collect data concerning the relationships established between actors and the extent to which these relationships impact actors' innovation capability. Results suggest that regional actors cannot be considered as a homogeneous group regarding their positioning in a regional network and that the innovation benefits of assuming different network positions depend on their nature. This paper offers some theoretical implications to the literature on regional innovation network and practical suggestions to organizations and regional policy makers.